Medical laboratory quality systems – a management review. Issue 3 (20th April 2015) - Theodorou, Dimitris; Giannelos, Padelis
Abstract : Purpose: – The purpose of this paper is to highlight changes in ISO 15189:2012 and ISO 15189:2007 concerning management review requirements and to present a management review checklist, which includes all the revised ISO 15189's requirements. Design/methodology/approach: – The recent revised and updated ISO 15189:2012 standard recommends a management review using a process approach and includes some additional topics. Findings: – The management review is a key element in many quality management systems, including medical laboratory management systems in accordance with ISO 15189. The process approach enables laboratory top managers and personnel to achieve all the quality management system's important inputs and outputs. Originality/value: – As laboratory staff often encounter difficulties fully exploiting the management review process, this checklist helps laboratory staff carry out an effective management review covering all the quality management system's important aspects.